(untitled) (Minerva, 2020)
Abstract: The aim of this work is to expound the contributions made by humanists Cristophoro Landino (1424-1498), Adrien Tournèbe (1512-1565) and Denis Lambin (1520-1572) to certain controversial passages from the Odes by Horace. The intention of this paper is to offer the Renaissance interpretation by these humanists on Horace. The main axes that structure this article are: the callida iunctura, the usus as ius and norma loquendi and the precept of respect for the mythical-historical tradition. These three Horatian principles are decisive for commentators to justify their amendments to the text.